Analysis of Non Formal Education Human Resources in Sup-port of Service and Quality Equality Education Programs in Sumedang Regency - Saepudin, Asep; Sukmana, Cucu; Ardiwinata, Jajat Sudrajat; Kamarubiani, Nike (Universitas Negeri Semarang, 2022)
This study is intended to provide an overview of the efforts to analyze the human resources of Non-Formal Education in supporting the service and quality of equality education programs. This research uses quantitative research methods with descriptive analysis methods and documentation study techniques. Data collection techniques used are interviews, observation and documentation. The results of this study indicate that the condition of the equality education program data in Sumedang Regency is quite good for equitable education services and there is a need for improvement and refinement to be able to improve the quality of equality education services in Sumedang Regency, then to describe the availability of human resources for equality education programs..Based on the existence of educators from the supply side, it shows that the availability of human resources is currently quite good and there needs to be improvements in efforts to improve the quality of education services, then to describe the quality of these human resources. resources for equivalence education programs based on academic qualifications and educator competencies. Currently, there is a shortage of education personnel which is a problem in educational services in equal distribution institutions.